A Missing Link in the Islamic Renaissance (American Journal of Islam and Society, 1991)
There is a missing link in Egypt. Although it is one of the strongestpillars upon which we are building our renaissance, we hardly ever perceiveits presence in our academic circles. This absence is one of the reasons forthe poverty of our scientific and intellectual production.And what is this missing link? To be precise, it is scholars who combinein their persons elements of both Arab-Islamic culture and the precise scientificEuropean culture. We are in need of more people like them, for we cannotregenerate ourselves without them, and we can only follow this path by makinguse of their light.Most of our scholars have only been educated in Arab-Islamic culture.As a result, they are totally ignorant of what is happening in the modemworld in relation to the opinions and views being expressed in science,literature, and philosophy. They have not heard of Kant and Bergson, or ofEurope’s authors and poets, scientists and researchers. At best, these namesare mentioned in insignificant magazines, newspapers, and books devoid ofany scientifichtellectual value. The other group of our scholars is madeup of those who have been educated solely in a foreign culture. They knowall about the latest theories in the fields of physics, chemistry, and mathematicswhich have reached them, and they follow the developments in modemEuropean literature as well as the books and poetry written by Europeans.They are also familiar with the development of philosophical views and theirprogress up to our time, but, they are totally ignorant of Arab-Islamic culture.If you tell them of Jarir, al Farazdaq, and al Akhtal, they turn their facesaway and avoid you-as if you were talking about a world not our own. Ifyou mention al Kindi, al Farabi, and Ibn Sina, they say that they have heardthe names but have no more knowledge of them, and that all we receivefrom them are ambiguous sentences and profound concepts which neitherhave scientific or intellectual benefit nor enrich or revitalize life.Yesterday I was talking with a group of these educated people about alBiruni, the Muslim mathematician who died in 440 AH, and the mathematicaland astronomical theories he had discovered. I also mentioned that the Germanorientalist Sachau had decided that al Biruni was the most brilliant man theworld has ever known, and that this orientalist had called for the establishmentof the al Biruni Society to honor him and to revitalize his memory. The people ...